Hate speech in secondary education: intellectual and emotional effects - Ramón Ortiz, Julia Ángela; Vilchez Guizado, Jesús (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The objective of this work is to analyze the influence of hate speech on the intellectual formation and emotional development of high school students. The methodology used responds to a field study with a sample of 64 students, a dichotomous questionnaire is administered and another adapted to the Likert scale referring to the dimensions of hate speech, intellectual and emotional development. The results show the proliferation of violence, discrimination and exclusion in secondary schools. It is concluded that the praxis of hate speech significantly influences the intellectual formation and emotional development of the student.